Social anxiety and suicidal ideation among middle-school students in China: a mediation model of internet addiction - Tan, Yafei; Deng, Jingjing; Zhang, Dan; Peng, Chang; Peng, Anna (Frontiers in Psychiatry, 2024)
Background: Suicide is a fatal public health issue for adolescents, and it is of great significance to explore the precursors of suicidal behaviors, especially suicidal ideation. However, the relationship between social anxiety and suicidal ideation and its mechanism are still unclear. The study aims to examine the association between social anxiety and suicidal ideation and the mediating effect through Internet addiction. Methods: A total of 2278 middle-school students aged 12 to 16 years were recruited through a multistage cluster sampling method in this cross-sectional study. Logistical regression analysis and structural equation modeling (SEM) were conducted to examine the direct and indirect effects of social anxiety. Results: During the past year, 262 (11.50%) participants reported suicidal ideation. Females had a higher prevalence of suicidal ideation than males (12.9% vs 10.0%, p =.034), and urban adolescents reported a higher prevalence than their rural counterparts (13.4% vs 9.6%, p =.006). In the total sample, social anxiety and Internet addiction were independently associated with suicidal ideation (p<.05). In the subgroup analysis, the association between social anxiety and suicidal ideation was significant only among rural females and urban males (p<.05). SEM demonstrated that social anxiety had direct and indirect effects on suicidal ideation, and Internet addiction partially mediated the relationship, with a mediating ratio of 30.53%. The partial mediating effect was also significant only in rural females and urban males. Conclusions: Adolescents may overuse the Internet to cope with social anxiety and further have suicidal ideation. Limiting Internet use and improving interpersonal skills in real life may be efficient for suicide prevention. In addition, targeted interventions should be tailored by different sexes across urban and rural regions.